Kyrgyz Republic Tax Legislation Influence on the Local Automotive Industry Efficiency - ABILPEISSOV, Kanash (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024DO - 10.14505/tpref.v15.3(31).15, 2024)
The issue of tax regulation of the automotive industry is relevant, as in the context of a dynamically developing global economy and rapid changes in the automotive industry, the issues of tax regulation become key to the effective functioning of the industry in any country, including the Kyrgyz Republic. The study aims to identify the relationship between tax legislation and the efficiency of the automotive industry in Kyrgyzstan, considering the current challenges and trends in the industry. The study employed various methods, including analytical, statistical, functional, system analysis, deduction, synthesis and comparison. The study analysed the impact of tax legislation on the efficiency of the automotive industry in the Kyrgyz Republic. The focus was on identifying the key aspects of tax regulation that have a direct impact on various areas of industry, including the investment climate, innovation activity and overall competitiveness of enterprises. A systematic analysis of existing tax mechanisms was conducted, the current state of the automotive industry in the country was analysed, and the impact of external factors such as dependence on imports, economic stability and changes in global trends, especially in the context of the development of electric vehicles, was identified. Tax mechanisms in the automotive industry, including customs duties, excise duties, and value-added taxes (VAT) are studied. Particular attention is devoted to the changes in tax legislation introduced in 2023 aimed at exempting parts supplies from VAT. The results of the study indicate the positive impact of such measures on the efficiency of car production.